Cadastro municipal, subsídios do geoprocessamento para a gestão pública – o exemplo do distrito de Warta, Londrina (PR) - Valmir de França; Ângela Canabrava Buchmann; Elizabeth Aparecida Alves; Alan Alves Alievi; José Paulo P. Pinese (Confins)
Control of different types of information about lots of rural and urban area of the municipality is of great importance for the planning of public policies aimed at developing local and regional planning. This article is a systematization of the WARTA-GIS Project, a partnership between City Hall of Londrina (PR) and the Center for Environmental Studies / Center of Exact Sciences, State University of Londrina (NEMA / CCE / UEL), among other organs. Aimed to demonstrate the efficiency of GIS as a tool for managing, it presents the implementation of this tool as a facilitator for the collection, analysis, storage and integration "online" of data as subsidies for decision-making. Specifically, wechose the district Warta - Londrina (PR) as the object of this study.